Highly crystalline TiO2 derived from titanate nanosheets for photocatalytic applications under various light sources - Zhou, Qiong. (2011)
Titanium dioxide (TiO2) is the most intensively used semiconductive material for photocatalysis, which is merely photoactive under the irradiation of UV light due to its wide band gap. The titanate nanosheets are synthesized from the alkaline hydrothermal treatment of P25 (TiO2) powders, analogous to the facile synthesis method for titanate nanotubes, but under a relatively moderate condition. The as-synthesized titanate nanosheets are then subjected to different treatment methods, in order to investigate the effects of treatment conditions, such as pH, temperature, and doping with nitrogen (N) species, on the phase, morphology and photocatalytic activity of the products. The experimental data about the treated products are collected from techniques including X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller (BET) and UV-Vis spectrometer. From the XRD analysis, it is observed that under moderate acidic and basic conditions, anatase is the only phase formed; whereas under strong acidic conditions, some brookite phase starts to form, and under strong basic conditions, some titanate phase remains. It is also observed that a progressive temperature increase results in a phase-transition sequence of protonated titanate, anatase and finally rutile, accompanied with an increase in their crystallinity.